The Role of Financial Literacy and Attitudes in Student Financial Management: Exploring Peer Influence as a Moderating Variable - Siti Komariah; Ely Masykuroh; Berlianto Haris (Journal of Islamic Economics (JoIE), 2025)
Introduction: This study examines the influence of financial literacy and attitudes on the financial management of FEBI IAIN Ponorogo students, with peers evaluated as a potential moderating factor. Amid increasing financial challenges in the digital era, understanding how peers influence students' financial behavior fills an important research gap. Research Methods: The research method was quantitative. The sample used was 100 respondents, obtained using the Slovin formula with a population of 2,684. The data collection technique was the use of questionnaires. Results: Financial literacy has a positive effect on financial management. Financial attitudes have a positive effect on financial management. Peers do not moderate the relationship between financial literacy and financial management. Peers cannot strengthen or weaken the relationship between financial literacy and financial management. Peers cannot strengthen or weaken the relationship between financial literacy and financial management. Conclusion: The findings highlight the importance of fostering financial literacy and positive attitudes among students, emphasizing the limited role of peers in shaping financial management behaviors.